Design And Implementation Of Error Correcting Codes For Transmission in Binary Symmetric Channel - Victor N. Papilaya (Bulletin of Electrical Engineering and Informatics, 2012)
Error Correcting codes are normally used for protecting transmitted information bits in a noisy channel. The information bits are encoded into error correcting codes which will be transmitted into the channel and on the receiver side, the received codes will be decoded back into the transmitted information bits. In this paper, a technique of generating binary error correcting codes that meet the Gilbert-bound and a simple encoding-decoding mechanism will be presented. To show the performance of the error correcting codes, a Binary Symmetric Channel is considered for transmission.